A multi-gap magnetorheological clutch with permanent magnet. (4th June 2015) - Rizzo, R; Musolino, A; Bucchi, F; Forte, P; Frendo, F
Abstract: This paper describes the design and testing of a novel permanent magnet clutch based on a magnetorheological fluid. It was inspired by a prototype previously developed by the authors and contains a novel gap shape conceived to reduce torque loss in the disengaged operating mode. Several geometries and material arrangements were investigated and the performance in terms of transmissible torque in different operating conditions was assessed using finite element numerical models. The prototype was manufactured and some experimental tests were performed. The new prototype was rated on the basis of performance indices and the design effectiveness was proven by a higher value of efficiency in the disengaged operating mode.